STUDENTS’ PERCEPTION ON THE USE OF ENGLISH MOVIES TO IMPROVE VOCABULARY MASTERY - Syahar Nurmala Sari; Dyah Aminatun (fsip.teknokrat.ac.id, 2021)
Since English has become an international language for communication, many people have used English to support their life goals. Someone who speaks foreign language including English must know the vocabulary of the language in order to be able to communicate properly. The use of the media in the process of teaching and learning English will attract students to study the language. One of the interesting media that can help students learn vocabulary is film or movie. It also offers information about an object and makes the classroom situation clear. This study is aimed to investigate students’ perception towards using movies to improve students’ vocabulary mastery. This study was conducted at Universitas Teknokrat Indonesia, Bandar Lampung. The main instruments used in the data collection were questionnaire and interview. The findings of the study indicate that students have positive perception towards the use of movies in their classes to improve their vocabulary mastery. Therefore, it can help them in improving their vocabulary acquisition in which in the end they will use it in their conversation or writing when they are using their English.